Online marketing and brand awareness for HEI: A review and bibliometric analysis [version 2; peer review: 2 approved] - Sailaja Bohara; Jyoti Sharma; Vashali Bisht; Pradeep Suri; Diksha Panwar; Sanjay Singh Chauhan (F1000Research)
Background This study conducted a comprehensive bibliometric analysis to identify the gaps in the existing literature related to Online marketing and brand awareness strategies for HEI. It has evaluated the current state of the literature on the given topic showing the pivotal role of online marketing and brand awareness in higher education for enrollment. Methods The study used a web-based application, Biblioshiny, which comes in the bibliometrix package. The study used the Scopus database to create the data set, given its conventional construction and quality of the sources. The analysis done is descriptive. By using the bibliometrix software, the study showed the authors name, articles, sources, citations, relevant journals and co-citation from the year 2017 to 2022. The time period selected by the study was five years which means that articles published from 2017 to 2022 have been taken for the study. Results We found that HEI online marketing and brand awareness have not been explored much as it has not reached the stage of maturity. Most of the publication was done during the time of Covid-19. Also, the role of brand awareness in student enrollment decisions for HEI requires more investigation. Top most publications their sources and top authors are identified. Conclusions Bibliometric analysis has provided valuable insights into the seminal work, emerging trends, and the gap in the study. This area of study has been explored but not as much as challenges, and the effectiveness of online marketing tools like seo, sem,ppc and more has not been measured. Further, this paper allows researchers to study by examining the pattern of publications by seeing the different authorships, co-authors, collaborations, relevant sources, and citations. The insights of this paper will help education policymakers devise more creative strategies to increase enrollment, ensuring sustained relevance and competitive advantage in higher education institutions .